Cultivating Productive Water in Valukai Aru Catchment in Valikamam Division of Jaffna District of Northern Sri Lanka - Visnuvarthanan, N.; Sivakumar, S. (International Journal of Scientific and Engineering Research, 2016)
Valukaiaru is a wet weather drainage scheme in the Jaffna peninsula. It is situated in the middle part of the Valikamam division. Valukaiaru basin has a total area of 57 sq. km covering the District Secretariat (DS) divisions of Tellipalai, Sandilipay, Chankanai and Uduvil. Valukaiaru scheme consists of a main drainage channel, eight tributary drainage channels and 65 minor tanks. The last control gate of this scheme, the Arali barrage is situated at the end of the channel at Arali. Valukaiaru starts from the village of Kurumpaciddy in Tellipalai DS Division and mixes with sea at the Arali barrage. Sea water intrusion through the damaged Arali barrage caused salinity problem in the soil and water resources of the Valukaiaru basin. Irrigation Department commenced the project on Rehabilitation of Arali barrage in 2008. By the renovation of Arali barrage sea water intrusion into the cultivable area through Valukaiaru has been stopped. Prevention of sea water intrusion significantly reduced the salinization of cultivatable lands and practicing effective water management will improve the productivity of the Agricultural Lands. The main causes that contribute to the low productivity of water and soil is improper management of water and agricultural practices, inadequate utilization of rainfall & sea water intrusion. More water is spilling without usage as there is not adequate capacity of tank although there is enough high and low lands for cultivation. This article analyses the problem and spell out a possible research solution to improve the water productivity of Valikamam.
Keywords: Rehabilitation; Water Management